Asteroseismic Observations of Hot Subdwarfs - Lynas-Gray, A. E. (Frontiers in Astronomy and Space Sciences, 2021)
There are a number of reasons for studying hot subdwarf pulsation; the most obvious being that these stars remain a poorly understood late-stage of stellar evolution and knowledge of their interior structure, which pulsation studies reveal, constrains evolution models. Of particular interest are the red giant progenitors as in looking at a hot subdwarf we are seeing a stripped-down red giant as it would have been just before the Helium Flash. Moreover, hot subdwarfs may have formed through the merger of two helium white dwarfs and their study gives insight into how such a merger may have happened. A less obvious reason for studying pulsation in hot subdwarfs is that they provide a critical test of stellar envelope opacities and the atomic physics upon which they depend.